2015
DOI: 10.1002/2014jg002805
|View full text |Cite
|
Sign up to set email alerts
|

Soil respiration sensitivities to water and temperature in a revegetated desert

Abstract: Soil respiration in water-limited ecosystems is affected intricately by soil water content (SWC), temperature, and soil properties. Eight sites on sand-fixed dunes that revegetated in different years since 1950s, with several topographical positions and various biological soil crusts (BSCs) and soil properties, were selected, as well as a moving sand dune (MSD) and a reference steppe in the Tengger Desert of China. Intact soil samples of 20 cm in depth were taken and incubated randomly at 12 levels of SWC (0 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 43 publications
(129 reference statements)
2
41
0
Order By: Relevance
“…Although desert ecosystem is generally low in soil organic carbon content, it plays an important role in soil carbon cycle (Liu et al, 2015). There are some recent researches on soil respiration in desert areas (e.g., Sierra, 2012;Jia et al, 2013;Zhang et al, 2015). A pervious study showed that soil respiration rate (Rs) in desert areas is relatively high in fixed sandy land, relatively low in semi-fixed sandy and lowest in shifting sandy land (Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although desert ecosystem is generally low in soil organic carbon content, it plays an important role in soil carbon cycle (Liu et al, 2015). There are some recent researches on soil respiration in desert areas (e.g., Sierra, 2012;Jia et al, 2013;Zhang et al, 2015). A pervious study showed that soil respiration rate (Rs) in desert areas is relatively high in fixed sandy land, relatively low in semi-fixed sandy and lowest in shifting sandy land (Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a significant hysteresis effect exists between Rs and Ts (Subke et al, 2003;Jia et al, 2013), and low levels of Ws could increase the degree of hysteresis (Phillips et al, 2011;Wang et al, 2013). Thus, Ws is of great importance in influencing Rs in desert ecosystems (Cable et al, 2011;Zhang et al, 2015). Recent studies proposed that desert ecosystems, which have long been neglected in the studies of global carbon budget, exhibit strong downward fluxes into the ground and therefore might be a significant carbon sink (Jasoni et al, 2005;Stone, 2008;Wohlfahrt et al, 2008;Ma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, other studies have investigated and quantified the impact of productivity on SR modeling [10, 11]. Apart from productivity, SR is influenced by different abiotic and biotic factors such as soil temperature, moisture, and microbial community, introducing a considerable uncertainty in SR estimates [12,13,14]. Among these factors, the temperature has been the most often studied factor affecting respiratory processes [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It plays an essential role in the soil organic matter distribution and may dampen the effects of climate change [14,22,23,24, 25]. In general, temperature declines with elevation, thus elevation gradient has been used to assess soil respiration response to temperature in several studies [12,26,27,28]. These studies indicate that CO2 exchange between soil and atmosphere varies along climatic gradients and that temperature sensitivity (Q10) of SR increases with elevation.…”
Section: Introductionmentioning
confidence: 99%
“…Castillo-Monroy et al (2011) used 5-cm-long TDR sensors and EC-5 sensors (Decagon Devices, Pullman, Wash.) installed vertically into the soil in several plots to measure water content. They found that the sensor provided reasonable estimates of volumetric water content at their field site, but their sensors may have sampled some biocrusts and soils below where biocrust is concentrated Zhang et al (2015). used 20-cm-long (Theta®) probes to measure water content of biocrusts and subsoil in the Tengger Desert of China.…”
mentioning
confidence: 99%